The dose of remimazolam combined with sufentanil for the induction of general anesthesia in obese patients undergoing bariatric surgery: an up-and-down sequential allocation trial - Chen, Minghui; Wang, Huiying; Sun, Jiajun; Zhang, Tao; Niu, Xiaoyin; Zhang, Tingting; Liu, Jian; Zhao, Xuan (Frontiers in Pharmacology, 2024)
Background and purpose: Remimazolam is a newly developed benzodiazepine drug with water-soluble, esterase degradation, and ultra-short-acting properties. The dose for general anesthesia induction in obese patients was not known. This study aimed to determine the optimal dose of remimazolam in combination with sufentanil for the induction of general anesthesia in obese patients. Methods: It was a prospective observational study. We recruited 46 patients scheduled for bariatric surgery from October 2022 to December 2023. One patient refused to provide informed consent, and six patients were receiving psychotropic medication. Thirty-nine patients were enrolled. The Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) scale was used to assess the patient’s response. The dose of sufentanil was 0.5 µg/kg (lean body weight [LBW]). The initial dose of remimazolam was 0.3 mg/kg (LBW). The dose of remimazolam was modified using the up-and-down allocation technique. Successful sedation (negative group) was characterized by achieving a MOAA/S score ≤ 1 within 3 min of commencing remimazolam infusion. If negative, the next patient received a low-level dose at a ratio of 0.9. Failed sedation (positive group) was defined as a MOAA/S score of >1 within 3 min of commencing remimazolam infusion. The patients in the positive group received propofol 0.5 mg/kg as a remedial measure, and the next dose was increased to a higher level. The primary outcome was to determine the half-effective dose (ED50) and 95% effective dose (ED95) of remimazolam in combination with sufentanil 0.5 µg/kg for induction in obese patients. The secondary outcome was to determine the occurrence of adverse effects such as hypotension, hypertension, and intraoperative awareness. Results: The ED50 and ED95 values of remimazolam (LBW) combined with sufentanil (0.5 µg/kg) (LBW) were 0.115 mg/kg (95% CI: 0.072–0.137) and 0.179 mg/kg (95% CI: 0.150–0.434), respectively, and the time of loss of consciousness in the negative group was 120.13 ± 25.03 s. The cardiovascular system was stable during the induction period. The incidence of post operative nausea and vomiting (PONV) was 38.5% in 39 patients. Respiratory depression, allergic reaction, intraoperative awareness, and delayed emergence were not observed in any patient. Conclusion: Remimazolam combined with sufentanil (0.5 µg/kg) (LBW) can be effectively used for general anesthesia induction in obese patients. The ED50 and ED95 values of remimazolam (LBW) were 0.115 mg/kg and 0.179 mg/kg, respectively. Clinical Trial Registration: www.chictr.org.cn, identifier ChiCTR2200065602.